Sacrum i profanum na tle krótkiej działalności Muzeum Diecezjalnego w Łomży - Grabowski, Tomasz (Archiwa, Biblioteki i Muzea Kościelne, 2016)
Diocesan Museum has been in Łomża since 2012. The first attempt to build it was made in 1925. The plan was to establish the museum as one building but the Diocese did not have enough money. Therefore, Museum had its place in Perish house. Then in 1981 Seminary and Pensioner Priests house was built. Diocesan Museum was to built next to the Priest House but unfortunately there was still no money. In 2009 the Bishop of Łomża Stanisław Stefanek after talks with bishop Tadeusz Bronakowski decided to run for European grant. Finally on 16th April 2012 Diocesan Museum was officially opened. The Museum is opened every day and it is visited by people who adore art especially sacral one. While visiting museum people have chance to come across regularly changed displays, sculptures and paintings. Museum organizes concerts of classical music and meetings with books’ authors. To sum up, Diocesan Museum is a great institution which teaches about Art, God and culture. So feel welcomed.